2019
DOI: 10.1371/journal.pone.0224768
|View full text |Cite
|
Sign up to set email alerts
|

Minimal effects of oyster aquaculture on local water quality: Examples from southern Chesapeake Bay

Abstract: As the oyster aquaculture industry grows and becomes incorporated into management practices, it is important to understand its effects on local environments. This study investigated how water quality and hydrodynamics varied among farms as well as inside versus outside the extent of caged grow-out areas located in southern Chesapeake Bay. Current speed and water quality variables (chlorophyll-a fluorescence, turbidity, and dissolved oxygen) were measured along multiple transects within and adjacent to four oys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 52 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…However, the breeding method of using ORs had only been introduced in the past 10 years. In previous studies, researchers found that oyster farming had a low impact on local water quality [34][35][36]. We verified this claim as follows.…”
Section: Impact Of Oyster Raftssupporting
confidence: 82%
“…However, the breeding method of using ORs had only been introduced in the past 10 years. In previous studies, researchers found that oyster farming had a low impact on local water quality [34][35][36]. We verified this claim as follows.…”
Section: Impact Of Oyster Raftssupporting
confidence: 82%
“…These mixed perceptions have been related to uncertainties about bivalve aquaculture interactions with coastal ecosystems (Mazur and Curtis 2008, D'Anna and Murray 2015, Flaherty et al 2019. Aquaculture environment interactions are site-specific and depend on the farmed biomass (Turner et al 2019, Filgueira et al 2021). There are cases in which aquaculture exceeded the carrying capacity of the system leading to several ecosystem impacts (Raillard andMénesguen 1994, Smaal et al 2001), and in other cases, bivalve aquaculture has minimized potential eutrophication (Guyondet et al 2015, Lavaud et al 2020.…”
Section: Drivers Of Social Acceptabilitymentioning
confidence: 99%
“…Despite potential benefits to aquatic ecosystems, marine bivalve farming can also negatively impact the production of ecosystem services. For example, metabolic waste products can cause eutrophication in poorly flushed areas (Turner et al 2019), and can reduce primary production through phytoplankton overgrazing when bivalves are at high stocking densities (Wijsman et al 2019). Ecosystem impacts stemming from bivalve aquaculture are thus context dependent and must be considered for each prospective site (Newell andKoch 2004, Guyondet et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Maryland, for example, 42% of total production in 2018 was derived from off-bottom gear (van Senten et al 2019). To date, studies conducted with off-bottom gear have demonstrated that this production mode contributes significant ESS, including habitat provision for local fish and invertebrate species (Marenghi & Ozbay 2010), biofiltration (Turner et al 2019), and biogeochemical cycling (Testa et al 2015). A more thorough review of ESS associated with shellfish aquaculture can be found elsewhere (e.g.…”
Section: Ess Of Oysters and Shellfish Aquaculturementioning
confidence: 99%